The Effect of Peat Soil on Shallow Groundwater Quality in Parit Nipah, Batu Pahat - Hassan, Nurul Hafizah; Ahmad Nazri, Mohd Ariff (Recent Trends in Civil Engineering and Built Environment, 2023)
Before realizing groundwater is potential for immense pollution from soil leachates of agricultures, thus drastically increase in ion and trace mineral concentrations, many people have used groundwater as one of their main sources of water and using them directly without any thought of filtering and processing. As the concerned of pollutant from human activities around Parit Nipah, Batu Pahat to contaminate the shallow groundwater below the peatland has become an inspiration to this study, there are mainly 2 objectives that are to be achieve, which is to determine the classification of shallow groundwater quality in terms of Cation and Anion and classify the types of the groundwater by using Piper Diagram approach. In this study, a series of laboratory test such as Atomic Absorption Spectrometer (AAS), Ion Chromatography (IC) and Water Quality testing such as temperature, pH and Dissolved Oxygen (DO) are done throughout the study. Analysis of the laboratory data are then evaluated using classifications of water quality and types of groundwater based on Interim National Water Quality Standards (INWQS) and plotting of Piper Diagram, respectively. From the data collected, the current state of the shallow well water was found strongly affected by the surrounding peat soil as results of the groundwater shows chemically and physically close to the characteristics of the soil itself. The plotting of Piper Diagram shows that the groundwater type of Parit Nipah area as Sodium-Chloride type (Na-Cl waters), where marine and deep ancient groundwaters are presence. Meanwhile from water quality parameter obtained, the sampled groundwater is classified as Class III based on the INWQS for Malaysia, whereas the water is suitable for agricultural, and livestock use and considered safe for human skin contact.